Modulation by Endothelin-1 of Spontaneous Activity and Membrane Currents of Atrioventricular Node Myocytes from the Rabbit Heart - Choisy, Stéphanie C.; Cheng, Hongwei; Smith, Godfrey L.; James, Andrew F.; Hancox, Jules C. (PLOS ONE, 2012)
Background The atrioventricular node (AVN) is a key component of the cardiac pacemaker-conduction system. Although it is known that receptors for the peptide hormone endothelin-1 (ET-1) are expressed in the AVN, there is very little information available on the modulatory effects of ET-1 on AVN electrophysiology. This study characterises for the first time acute modulatory effects of ET-1 on AVN cellular electrophysiology. Methods Electrophysiological experiments were conducted in which recordings were made from rabbit isolated AVN cells at 35–37°C using the whole-cell patch clamp recording technique. Results Application of ET-1 (10 nM) to spontaneously active AVN cells led rapidly (within ∼13 s) to membrane potential hyperpolarisation and cessation of spontaneous action potentials (APs). This effect was prevented by pre-application of the ETA receptor inhibitor BQ-123 (1 µM) and was not mimicked by the ETB receptor agonist IRL-1620 (300 nM). In whole-cell voltage-clamp experiments, ET-1 partially inhibited L-type calcium current (ICa,L) and rapid delayed rectifier K+ current (IKr), whilst it transiently activated the hyperpolarisation-activated current (If) at voltages negative to the pacemaking range, and activated an inwardly rectifying current that was inhibited by both tertiapin-Q (300 nM) and Ba2+ ions (2 mM); each of these effects was sensitive to ETA receptor inhibition. In cells exposed to tertiapin-Q, ET-1 application did not produce membrane potential hyperpolarisation or immediate cessation of spontaneous activity; instead, there was a progressive decline in AP amplitude and depolarisation of maximum diastolic potential. Conclusions Acutely applied ET-1 exerts a direct modulatory effect on AVN cell electrophysiology. The dominant effect of ET-1 in this study was activation of a tertiapin-Q sensitive inwardly rectifying K+ current via ETA receptors, which led rapidly to cell quiescence.